Influenza Vaccine Effectiveness for Fully and Partially Vaccinated Children 6 Months to 8 Years Old During 2011–2012 and 2012–2013: The Importance of Two Priming Doses. Issue 3 (March 2016) - Thompson, Mark G.; Clippard, Jessie; Petrie, Joshua G.; Jackson, Michael L.; McLean, Huong Q.; Gaglani, Manjusha; Reis, Evelyn C.; Flannery, Brendan; Monto, Arnold S.; Jackson, Lisa; Belongia, Edward A.; Murthy, Kempapura; et al.
Abstract : Background: Few studies have examined the effectiveness of full versus partial vaccination with inactivated trivalent influenza vaccines (IIV3) as defined by the US CDC Advisory Committee on Immunization Practices. Methods: Respiratory swabs were collected from outpatients aged 6 months to 8 years with acute cough for ⩽7 days in clinics in 5 states during the 2011–2012 and 2012–2013 influenza seasons. Influenza was confirmed by real-time reverse transcription polymerase chain reaction assay. Receipt of current season IIV3 and up to 4 prior vaccinations was documented from medical records and immunization registries. Using a test-negative design, vaccine effectiveness (VE) was estimated adjusting for age, race/ethnicity, medical conditions, study site and month of enrollment. Results: We did not observe higher VE for children fully versus partially vaccinated with IIV3, as defined by US Advisory Committee on Immunization Practice, although our sample of partially vaccinated children was relatively small. However, among children aged 2–8 years in both seasons and against A(H3N2) and B influenza illness separately, VE point estimates were consistently higher for children who had received 2 doses in the same prior season compared with those without (VE range of 58%–80% vs. 33%–44%, respectively). Across seasons, the odds of A(H3N2) illness despite IIV3 vaccination were 2.4-fold (95% confidence interval: 1.4–4.3) higher among children who had not received 2 doses in the same prior season. We also noted residual protection among unvaccinated children who were vaccinated the previous season (VE range = 36%–40% across outcomes). Conclusion: Vaccination with IIV3 may provide preventive benefit in subsequent seasons, including possible residual protection if vaccination is missed. Two vaccine doses in the same season may be more effective than alternative priming strategies. Abstract : Supplemental Digital Content is available in the text.